2012
DOI: 10.1093/rheumatology/kes102
|View full text |Cite
|
Sign up to set email alerts
|

Anti-MDA5 antibody, ferritin and IL-18 are useful for the evaluation of response to treatment in interstitial lung disease with anti-MDA5 antibody-positive dermatomyositis

Abstract: Anti-MDA5ab titre and ferritin and IL-18 concentrations are useful for the evaluation of the response to treatment and the status of ILD in patients with anti-MAD5ab-positive DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
231
5
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 291 publications
(248 citation statements)
references
References 26 publications
6
231
5
6
Order By: Relevance
“…Anti-MDA5-positive-dermatomyositis (anti-MDA5-positive-DM) was first described in a group of patients who lacked clinical signs of muscle involvement (clinically amyopathic dermatomyositis); however, subsequent studies have also found patients with this antibody who have classic muscle involvement with weakness and elevated muscle enzymes. [6][7][8][9][10][11] Anti-MDA5-positive-DM patients typically present with prominent skin manifestations, including heliotrope rash, Gottron's papules as well as cutaneous ulceration and tender palmar papules, the latter of which are unique to anti-MDA5-positive-DM (Table 1). 6,[12][13][14] Oral manifestations-including oral ulceration, mucosal pain, and hoarseness-are common, as are arthritis, arthralgia, and fever.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anti-MDA5-positive-dermatomyositis (anti-MDA5-positive-DM) was first described in a group of patients who lacked clinical signs of muscle involvement (clinically amyopathic dermatomyositis); however, subsequent studies have also found patients with this antibody who have classic muscle involvement with weakness and elevated muscle enzymes. [6][7][8][9][10][11] Anti-MDA5-positive-DM patients typically present with prominent skin manifestations, including heliotrope rash, Gottron's papules as well as cutaneous ulceration and tender palmar papules, the latter of which are unique to anti-MDA5-positive-DM (Table 1). 6,[12][13][14] Oral manifestations-including oral ulceration, mucosal pain, and hoarseness-are common, as are arthritis, arthralgia, and fever.…”
Section: Discussionmentioning
confidence: 99%
“…6,7,12,14,16 In comparison to other patients with dermatomyositis and ILD, anti-MDA5-positive-DM patients are more likely to have rapidly progressive disease. 7,8 The development and rapid progression of ILD may account for the significantly higher mortality observed in anti-MDA5-positive-DM patients as compared to serologically negative cohorts. 6,14,18,19 Generally, skin manifestations precede ILD in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Gono et al (2) reported that a high ferritin level on admission was a poor prognostic factor in RPIP patients with DM, including anti-MDA5 antibody ADM. Regarding autoimmune disorders, the highest ferritin levels have been reported in patients with macrophage activation syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-MDA5 antibody is closely related to rapidly progressive interstitial pneumonitis (RPIP) associated with amyopathic dermatomyositis (ADM), particularly in Asian populations. RPIP secondary to ADM can be resistant to aggressive therapy and sometimes even fatal (2). Here, we report a case of anti-MDA5 antibody-positive ADM associated with RPIP and discuss high-dose intravenous immunoglobulin (IVIg) therapy as a possible therapeutic agent.…”
Section: Introductionmentioning
confidence: 99%
“…В случае гипомиопатического варианта ДМ предполагается возможность субклинического поражения мышечной тка-ни, выявляемого при целенаправленном обследовании маркеров миозита, включая игольчатую электромиогра-фию (и-ЭМГ), биопсию и магнитно-резонансную томо-графию (МРТ) мышц. CADM чаще встречается у азиатско-го населения [18,19] и ассоциирован с высокой частотой быстропрогрессирующего ИПЛ (13-14%). Позитивность по анти-CADM-140 (MDA5) антителам рассматривается как фактор риска ИПЛ [20].…”
Section: классификацияunclassified